CREATIVE TYPES OF SPEECH ADVERTISING SLOGAN AS A TEXT “WITH A CREATIVE TASK” - Mikheeva, E.S. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The urgency of the work is due to the fact that modern speech activity has a distinct creative character. The research of the creative potential itself in the linguistic system, on the one hand, and linguistic identity (the speaker), on the other, is one of actual directions of modern linguistics. The different definitions of types of speech cannot give a full description of the variety of types of modern Russian speech. One of the steps towards a modern perspective on this issue is the selection and description of creative styles of speech that have a differential feature as the creative transformation of language units into the facts of speech. The appeal to the sphere of creative types of speech allows to understand a new perspective on the main language features. So in modern linguistics is being formed the representation of creative function, therefore there is a need of analysis of this feature in the aspect of its interaction with aesthetic function and linguistic manipulation. Analysis of the implementation of these functions in creative types of speech allows to identify texts with an imaginative task (with imagery in a broad sense), where the realization of the aesthetic function is a necessary condition, and the texts with a creative task, characterized by the realization of creative functions, as well as linguistic manipulation. Despite the fact that some advertising slogans can be combined with several imaginative means to talk about their aesthetic values, ad-vertising slogans should be attributed to the texts with a creative task.